Detection and transmission of Fusarium verticillioides in corn seeds according to the plant stage - Sousa, Rosângela Ribeiro de (2021)
The objective of this study was to evaluate the transmissibility of F. verticillioides, in corn seeds, when inoculated in different phenological stages. The plants were inoculated with the pathogen at the following stages: V7, V9, R1, R2, R4, and R6. The experiments were conducted in pots, in a completely randomized design, with six replications. The fungus infection rate in the seeds was verified through the health test (Blotter Test). The significance of the contrast between the phenological stages and in the two experiments (rainy season and dry season), and productivity showed plant-seed transmission of F. verticillioides in all phenological stages. The PCR technique was able to reveal up to the lowest level, 1% incidence of F. verticillioides in corn seeds. There was a significant difference between the times of plant inoculation and the incidence of the fungus in the seeds. Plants inoculated in the reproductive phase transmitted F. verticillioides for seeds with the highest rate of infection, in the two experiments, in the rainy season (V7 - 48; V9 - 46; R1 - 77.33; R2 - 84; R4 - 96; R6 - 96.67; and Test - 14.67%), and dry season (V7 - 46.67; V9 - 66; R1 - 75.33; R2 - 95.33; R4 - 98; and R6 - 97.33%). In this way, the present work demonstrated that in the reproductive phenological stages R2, R4, and R6, the corn plant was more susceptible to infection with F. verticillioides, and that it also resulted in a decrease in grain productivity.